Kemampuan Pemecahan Masalah Matematika Ditinjau dari Disposisi Matematis Siswa Kelas VII SMPN 7 Bukittinggi - Putri, Rayla Osvita; Rahmat, Tasnim; Imamuddin, M.; Medika, Gema Hista (Indo-MathEdu Intellectuals Journal, 2024)
This research is based on the low mathematical problem-solving ability of students, one of which is because during the learning process students tend to be silent and not confident when answering the practice questions given, there is no courage to answer every question given. The purpose of this study is to find out students' mathematical problem-solving ability reviewed from mathematical disposition. This type of research is a qualitative description research. The research subjects were selected 3 students out of 29 students, namely, one student for each category of mathematical disposition, including high, medium, and low mathematical disposition categories. The instruments used are questionnaire instruments, mathematical problem-solving ability tests, and interview guidelines. The data analysis techniques used are data reduction, data presentation and conclusion drawn. The data validity technique used is triangulation technique. Based on the results of this study, students with a high category of mathematical disposition have a level of mathematical problem-solving ability with a very good category. Then students with a moderate category of mathematical disposition have a level of mathematical problem-solving ability with a sufficient category. Furthermore, students with a low category of mathematical disposition have a different level of mathematical problem-solving ability, which is less and less